Biochemical basis of resistance in eggplant (Solanum melongena L.) to Leucinodes orbonalis Guenee and their correlation with shoot and fruit infestation (Bangladesh Journal of Agricultural Research, 2010)
Studies on the biochemical basis of resistance to Leucinodes orbonalis Guenee and their correlation with shoot and fruit borer damage in five selected brinjal genotypes done at Tamil Nadu Agricultural University, India during June to December 2005 showed that both shoot and fruit of less susceptible genotypes had the higher amount of poly phenol oxidase (PPO), phenylalanine ammonium lyase (PAL) and lignin and lower amount of reducing sugar. Significant negative correlation was found between percent infestation (shoot and fruit) with PPO, PAL and lignin content, whereas it was positively correlated with reducing sugar content. Among the biochemical constituents, PPO, PAL and lignin contents were negatively correlated with reducing sugar but PPO were positively correlated with PAL and lignin content and vice-versa. Keywords: Biochemical basis; resistacace; eggplant; Leucinodes orbonalis. DOI: 10.3329/bjar.v35i1.5876Bangladesh J. Agril. Res. 35(1) : 149-155, March 2010